الطابع الزخرفي في العمارة الاسلامية - تواتي, إيناس (كلية الأدب العربي والفنون, 2025)
تُعد الزخرفة عنصراً أساسياً في العمارة الإسلامية، إذ لا تقتصر وظيفتها على التزيين فحسب، بل تعبّر عن بُعد رمزي وروحي يعكس رؤية حضارية متجذّرة في الثقافة الإسلامية. وتُجسد المباني الدينية، تهدف هذه الدراسة إلى تحليل الطابع الزخرفي في العمارة الإسلامية من خلال اختيار المسجد الأعظم بالجزائر العاصمة كنموذج تطبيقي، وذلك بغرض إبراز الأبعاد الجمالية والرمزية التي تعكسها الزخرفة في الفضاءات المعمارية الإسلامية. وقد توصلت هذه الدراسة إلى أن المسجد الأعظم يجسد تنوعاً زخرفياً ثريا حيث تندمج العناصر الهندسية والنباتية والكتابية في تشكيل وحدة فنية ً يتكامل فيها البُعد الجمالي مع الروحاني؛ويُبرز هذا التنوع الزخرفي مدى التزام العمارة الإسلامية بالفن كوسيلة للتعبير عن القيم الدينية والثقافية والجمالية في آن واحد. Ornamentation is a fundamental component of Islamic architecture, extending beyond mere decoration to express a symbolic and spiritual dimension deeply rooted in Islamic cultural identity. Religious buildings, particularly mosques, represent this artistic expression in its most profound form. This study aims to analyze the ornamental character of Islamic architecture by examining the Great Mosque of Algiers as a case study. The objective is to highlight the aesthetic and symbolic dimensions conveyed through ornamentation in Islamic architectural spaces. The findings reveal that the mosque showcases a rich diversity of decorative elements, harmoniously blending geometric, vegetal, and calligraphic motifs into a unified artistic whole, where visual beauty and spiritual depth converge. This ornamental diversity underscores the commitment of Islamic architecture to art as a medium for expressing religious, cultural, and aesthetic values.
دراسة المسجد الاعظم بالجزائر العاصمة أنموذجا
Keywords: الطابع الزخرفي – العمارة الإسلامية – المساجد – فن الزخرفة; ornamental character – Islamic architecture – mosques – decorative art